2015
DOI: 10.2215/cjn.00980115
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Potassium Excretion and Renal and Cardiovascular Complications in Patients with Type 2 Diabetes and Normal Renal Function

Abstract: Background and objectives We investigated the association of urinary potassium and sodium excretion with the incidence of renal failure and cardiovascular disease in patients with type 2 diabetes.Design, setting, participants, & measurements A total of 623 Japanese type 2 diabetic patients with eGFR$60 ml/min per 1.73 m 2 were enrolled in this observational follow-up study between 1996 and 2003 and followed-up until 2013. At baseline, a 24-hour urine sample was collected to estimate urinary potassium and sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 28 publications
2
60
1
Order By: Relevance
“…Physiologically, the elderly are more susceptible to AKI, and it is important to understand the association of this pathology with a more or less severe consequence for this population (25) . The strict control of hypertension and diabetes is a strategy that should reduce the risk of renal complications (26) . In addition, a study showed hypertension and diabetes are risk factors for AKI (27) .…”
Section: Resultsmentioning
confidence: 99%
“…Physiologically, the elderly are more susceptible to AKI, and it is important to understand the association of this pathology with a more or less severe consequence for this population (25) . The strict control of hypertension and diabetes is a strategy that should reduce the risk of renal complications (26) . In addition, a study showed hypertension and diabetes are risk factors for AKI (27) .…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis has recently been addressed in 6 large CKD cohorts (Table 1) [11][12][13][14][15][16]. Smyth et al [13] performed their analysis in the ONTARGET and TRANSCEND cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that dietary intake is not the primary determinant of serum K + in CKD and adds to the safety of our proposed K + supplementation trial. Araki et al [11] analyzed the association between 24-h urinary K + excretion, renal outcomes, and CV events in Japanese patients with type 2 diabetes. During a median follow-up of 11 years, patients in the highest quartile of urinary K + excretion (>2.9 g/day) had significantly fewer CV events, 50% reduction in eGFR, or start of renal replacement therapy than patients in the lowest quartile (< 1.72 g/day).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations